Cases in Precision Medicine: The Role of Polygenic Risk Scores in Breast Cancer Risk Assessment - Zeinomar, Nur (Ann Intern Med, 2020)
Polygenic risk scores (PRS) have been consistently associated with elevated breast cancer risk in cohort studies and are associated with risk in both women with and without a family history of breast cancer. However, before clinical implementation we need to address several issues including understanding the potential clinical utility and the optimal method to communicate personalized screening recommendations that incorporate the PRS. Several trials are currently underway to answer some of these questions and facilitate clinical implementation. Since these PRSs have been developed in European ancestry women, an important question is to understand the limitations of the predictive ability of these PRSs to other ancestral groups. Finally, the value of PRS will lie in considering it along with other clinical, familial, and rare genetic factors that are currently used in personalized risk assessment of breast cancer.